2010
DOI: 10.1016/j.tvjl.2009.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Functional response to inhaled salbutamol and/or ipratropium bromide in Ascaris suum-sensitised cats with allergen-induced bronchospasms

Abstract: a b s t r a c tKnowledge about the use of inhaled bronchodilators in cats with so-called 'feline asthma' is limited and relies on the experience of clinicians treating these patients. A randomised controlled four-way crossover study was therefore designed to compare the effects of salbutamol (SAL, 100 lg), ipratropium bromide (IB, 20 lg) and a combination of both (SAL/IB, 100 lg/20 lg), delivered through a pressurised metereddose inhaler (pMDI) connected to a spacing chamber, on allergen-induced bronchospasms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
14
0
4
Order By: Relevance
“…23,25,27,[29][30][31][32][33][34][35] Of the prospective studies, 19 were open and uncontrolled 24,28,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] while 29 were randomised, controlled [53][54][55][56][57][58][59] and often blinded. 26,42,[60][61][62][63][64][65][66][67][68][69][70][71][72][73]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23,25,27,[29][30][31][32][33][34][35] Of the prospective studies, 19 were open and uncontrolled 24,28,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] while 29 were randomised, controlled [53][54][55][56][57][58][59] and often blinded. 26,42,[60][61][62][63][64][65][66][67][68][69][70][71][72][73]…”
Section: Resultsmentioning
confidence: 99%
“…69 In the cross-over study with five cats sensitised to A. suum, enhanced pause, an estimator of airflow limitation measured by BWBP, was repeatedly assessed within 120 min following the administration of each treatment protocol. 70 Responses to inhaled medications were evaluated by calculating the area under the time-response curves (AUC) from 0 to 60 or 120 min after drug administration (AUC 0-60 , AUC 0-120 ), as well as the times required for half-recovery or for returning to nearly basal conditions. There was no difference in time-related bronchodilating effects between 100 mcg salbutamol, 20 mcg ipratropium bromide, a combination of the two treatments, and the nontreated control.…”
Section: Analysis Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…19 An injectable short-acting beta-2 agonist such as terbutaline is preferred by the authors in cats with status asthmaticus as bronchospasm limits delivery of inhaled bronchodilators to the lower airways. 48 Once the life-threatening crisis has passed, these cats are managed as stable asthmatics. For additional information on feline asthma treatment, including research on novel therapies, the reader is referred to other reviews.…”
Section: Treatmentmentioning
confidence: 99%
“…Simultaneous visual inspection (SVI) of BWBP waveforms, and the recognition and manual elimination of artefactual waveforms that are not automatically detected by the software, have been described in one study with healthy dogs, 18 while many studies in cats have reported that disturbed waveforms were automatically eliminated by the software under similar rejection criteria (when TV <5–10 ml, when Ti <0.15 s or >10 s, or when the difference between inspiratory and expiratory volumes exceeds 20%). 5,6,8,19,20 Although the BWBP system has been applied in clinical studies using client-owned cats, 913,21 it is not known whether the commonly used rejection criteria are sufficient for excluding most non-breath artefacts, which may affect the final outcome in these clinical cases. The present study was designed to evaluate the effect of SVI on BWBP waveforms on the results obtained from the examinations.…”
Section: Introductionmentioning
confidence: 99%